2005
DOI: 10.1088/0953-2048/18/7/009
|View full text |Cite
|
Sign up to set email alerts
|

The design and performance of a Bi-2223/Ag magnet cooled by a single-stage cryocooler

Abstract: The design and fabrication of a split coil Bi-2223/Ag tape superconducting magnet cooled by a single-stage cryocooler is presented. The magnet consists of six double-wound pancakes impregnated by epoxy resin with inner diameter 50 mm and outer diameter 98 mm. Critical currents of individual pancakes, double pancakes and the whole magnet are measured, calculated and discussed. The magnet's performance was tested at liquid helium and nitrogen temperatures as well as at solid nitrogen temperatures and cooled by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In 2006, after the final test of a Phase 2 700 MHz LTS/HTS NMR magnet, we found a remanent magnetic field of 0.02 T or an equivalent NMR frequency of 0.85 MHz, even after both magnets were completely discharged at 4.2 K. Based on a simple assumption, accompanied by calculation, we concluded that the remanent field is generated by a screening-current-induced magnetic field (SCF) and furthermore an SCF could be a major source of field impurities in the two LTS/HTS NMR magnets completed to date in this 3-phase program, a 350 MHz magnet (Phase 1) and 700 MHz (Phase 2) [4]. A remanent field in an HTS magnet has been studied [5], [6], mainly focused on the magnitude of the self-field induced SCF at the HTS magnet center. For NMR magnets that require a highly homogeneous field distribution, the axial distribution and field gradients of an SCF, either external-field or self-field induced, and their effects on field homogeneity are critically important.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, after the final test of a Phase 2 700 MHz LTS/HTS NMR magnet, we found a remanent magnetic field of 0.02 T or an equivalent NMR frequency of 0.85 MHz, even after both magnets were completely discharged at 4.2 K. Based on a simple assumption, accompanied by calculation, we concluded that the remanent field is generated by a screening-current-induced magnetic field (SCF) and furthermore an SCF could be a major source of field impurities in the two LTS/HTS NMR magnets completed to date in this 3-phase program, a 350 MHz magnet (Phase 1) and 700 MHz (Phase 2) [4]. A remanent field in an HTS magnet has been studied [5], [6], mainly focused on the magnitude of the self-field induced SCF at the HTS magnet center. For NMR magnets that require a highly homogeneous field distribution, the axial distribution and field gradients of an SCF, either external-field or self-field induced, and their effects on field homogeneity are critically important.…”
Section: Introductionmentioning
confidence: 99%
“…The coil is a basic unit for a magnet used in a maglev demonstration vehicle [7]. The coil is designed primarily for a non-eddy current structure, therefore any usage of metallic material is absent from the main structure including the copper bobbin, which is frequently used not only as a skeleton but also as a cooling path in some DC magnets [8][9][10]. The absence of the bobbin in this design also shortens the distance between the iron core and HTS coils, and thereby reduces the flux leakage as much as possible.…”
Section: Hts Coil Design and Fabricationmentioning
confidence: 99%
“…We have proposed design criteria and finite element analysis (FEM) of a split-coil Bi2223/Ag tape superconducting magnet cooled by a single stage cryocooler [4]. This technology had demonstrated capability for reliable performance of the magnet without training.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information about the magnet design and properties are specified in our previous paper [4]. In this work we present a new laboratory cryostat system designed for this magnet assembly as well as calculated properties of the magnet with added iron concentrators.…”
Section: Introductionmentioning
confidence: 99%